086 Assessment of ischaemic burden in patients with three-vessel coronary artery disease using high-resolution myocardial perfusion cardiovascular MRI. (16th May 2012) - Motwani, M; Fairbairn, T A; Maredia, N; Kozerke, S; Greenwood, J P; Plein, S
Abstract : Introduction: Patients with three-vessel disease (3VD) have a worse prognosis than those with less extensive disease; but detecting a 3VD pattern of ischaemia can be very challenging due to balanced hypoperfusion. However, a large ischaemic burden can also correctly stratify patients with 3VD as high-risk and prompt the appropriate management. We hypothesised that high-resolution perfusion-CMR would detect more ischaemic burden than standard-resolution due to better detection of subendocardial ischaemia. This study compared ischaemic burden detected by standard-resolution and high-resolution cardiovascular magnetic resonance (CMR) perfusion imaging in patients with 3VD. Methods: CAD was defined as coronary stenosis >70% (QCA). 48 patients (24 with 3VD; 24 with no CAD) underwent stress/rest perfusion-CMR (1.5T Philips) with standard-resolution (2.5 mm in-plane) using twofold SENSE and on a separate visit high-resolution (1.6 mm in-plane) achieved by eightfold k-t broad linear speed up technique (BLAST) acceleration (Abstract 086 figure 1 ). Perfusion was visually graded in each segment on a 5-point scale and summed to produce a perfusion score for each patient. Results: In the 3VD group, high-resolution identified more abnormal segments per patient (7.3±3.7 vs 5.2±3.9; p=0.01), more abnormal territories per patient (2.0±0.9 vs 1.46±1.0; p=0.02) and a higher overall perfusion score (17.7±8.6 vs 13.9±10.2; p=0.03). The number of segments with subendocardial ischaemia was greater for high-resolution (134 vs 70 segments; 47% vs 24%; p<0.001) (Abstract 086 figure 2 ). The sensitivity, specificity and area under the curve (AUC) for identifying any perfusion defect were similar for both methods (high-resolution: 92%, 74% and 0.94 respectively vs standard-resolution: 79%, 84% and 0.87; p>0.05). Conclusion: In patients with 3VD, high-resolution perfusion-CMR detected more ischaemic burden than standard-resolution by identifying more segments with subendocardial ischaemia. High-resolution perfusion-CMR therefore has incremental value in correctly stratifying this high-risk patient group.